Validation of the brave hand writing kinder (BHK): a tool for measuring arabic handwriting - Anis ben Chikha; Ghazwa ben Maaouia; Aymen Hawani (Technium Social Sciences Journal, 2020)
Handwriting is a complex skill that has been developing over time. To learn handwriting, children need to combine motor skills, memory, attention, visuomotor integration and other cognitive functions. The readability of writing can affect teachers’ assessment of academic achievement and children’s self-esteem about their ability to produce texts. Referring to the practice of Tunisian school education we find that there I a lack of scientific references to discern when the difficulties of Handwriting transits from normality to abnormality. So far we have no scale of criteria evaluating this gesture in Arabic writing. The aim of this study is to have a means of evaluating the performance of Handwriting of the Tunisian student in two measurable dimensions namely quality and speed. Thus, we undertake a validation methodology of a measurement tool on a population with varied characteristics and ordinarily representative of the Tunisian child in the six levels of primary school (age: 6.6 - 11.8). In fact, we chose to validate the Brave Handwriting Kinder (BHK) from its French version translated by Charles, Soppelsa&Albaret in (2003). The scale also makes it possible to establish a rapid and early diagnosis of writing disturbances of the child and thus to identify premature disorders related to the functions of Handwriting.